Volunteers work together to clean river - Nor Salwana, Mohammad Idris (2021)
KUANTAN, 27 March 2021 - Recognising the importance of river sustainability, Universiti Malaysia Pahang (UMP) and the Pahang State Department of Environment (DOE) have held various efforts to rehabilitate and maintain river cleanliness.